Characterization of a sesquiterpene cyclase from the glandular trichomes of Leucosceptrum canum for sole production of cedrol in Escherichia coli and Nicotiana benthamiana. (June 2019) - Luo, Fei; Ling, Yi; Li, De-Sen; Tang, Ting; Liu, Yan-Chun; Liu, Yan; Li, Sheng-Hong
Abstract: Cedrol is an extremely versatile sesquiterpene alcohol that was approved by the Food and Drug Administration of the United States as a flavoring agent or adjuvant and has been commonly used as a flavoring ingredient in cosmetics, foods and medicine. Furthermore, cedrol possesses a wide range of pharmacological properties including sedative, anti-inflammatory and cytotoxic activities. Commercial production of cedrol relies on fractional distillation of cedar wood oils, followed by recrystallization, and little has been reported about its biosynthesis and aspects of synthetic biology. Here, we report the cloning and functional characterization of a cedrol synthase gene ( Lc-CedS ) from the transcriptome of the glandular trichomes of a woody Lamiaceae plant Leucosceptrum canum . The recombinant Lc-CedS protein catalyzed the in vitro conversion of farnesyl diphosphate into the single product cedrol, suggesting that Lc-CedS is a high-fidelity terpene synthase. Co-expression of Lc-CedS, a farnesyl diphosphate synthase gene and seven genes of the mevalonate (MVA) pathway responsible for converting acetyl-CoA into farnesyl diphosphate in Escherichia coli afforded 363 μg/L cedrol as the sole product under shaking flask conditions. Transient expression of Lc-CedS in Nicotiana benthamiana also resulted in a single product cedrol with a production level of 3.6 μg/g fresh weight. The sole production of cedrol by introducing of Lc-CedS in engineered E. coli and N. benthamiana suggests now alternative production systems using synthetic biology approaches that would better address sufficient supply of cedrol. Graphical abstract: A sesquiterpene cyclase for sole production of cedrol using synthetic biology approaches.Image 1 Highlights: A high-fidelity cedrol synthase was cloned and identified from Leucosceptrum canum. Escherichia coli harboring Lc-CedS produced 363 μg/L cedrol as a single product. Nicotiana benthamiana expressing Lc-CedS produced cedrol with a yield of 3.6 μg/g FW.